Predicting school readiness program implementation in community-based childcare centers - Hunter, Leah J.; Bayly, Benjamin L.; Bierman, Karen L.; Welsh, Janet A.; Gest, Julia M. (Frontiers in Psychology, 2022)
Introduction Targeted curricular interventions can increase preschool program quality and boost children’s academic and social–emotional readiness skills, but variable funding and weak organizational infrastructure in many community-based childcare centers may reduce the effective implementation of these programs. Method This study examined individual teacher and workplace predictors of the REDI program implementation, a targeted school readiness program that was adapted to support delivery in childcare centers. REDI was delivered by 63 teachers in 37 community-based childcare centers with center directors serving as local implementation coaches. Results Results showed that individual teacher factors (e.g., teaching skills and receptivity to intervention consultation) predicted the quality with which REDI activities and teaching strategies were delivered, and workplace factors were important predictors across multiple implementation indicators. Discussion Practice and policy implications for improving intervention implementation and corresponding program quality in childcare centers are highlighted.